1977
DOI: 10.1172/jci108692
|View full text |Cite
|
Sign up to set email alerts
|

Adenylate cyclase of human fat cell ghosts. Stimulation of enzyme activity by parathyroid hormone.

Abstract: A B S T R A C T Some of the effects of native bovineparathyroid hormone and of the synthetic aminoterminal 1-34 fragment on the adenylate cyclase activity of human fat cell ghosts were studied. Saturating concentrations of both hormone preparations caused a significant increase of enzyme activity by about 200-300%. Guanosine 5'-triphosphate (0.1 mM) inhibited basal enzyme activity but had no substantial effect on parathyroid hormone-stimulated enzyme activity. The guanosine 5'-triphosphate analogue, 5'-guanyly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Experimental procedures were the same as described, (8). Fat cells and fat cell ghosts were prepared according to Rodbell (9).…”
Section: Methodsmentioning
confidence: 99%
“…Experimental procedures were the same as described, (8). Fat cells and fat cell ghosts were prepared according to Rodbell (9).…”
Section: Methodsmentioning
confidence: 99%
“…Experimental procedures were essentially the same as in [6] . Fat cells and fat cell ghosts were prepared according to [lo] .…”
Section: Methodsmentioning
confidence: 99%
“…Experimental procedures were the same as described previously [10]. Fat cells and fat cell ghosts were prepared according to Rodbell [15].…”
Section: Methodsmentioning
confidence: 99%
“…Since prostaglandins are synthesized in response to lipolytic hormones [4,5], feed-back inhibition of the adenylate cyclase has been proposed as the mechanism underlying the antilipolytic effects of these C-20 fatty acids [1]. As opposed to this concept, we have recently found that prostaglandins of the E-and 0300-9130/79/0176/0025/$ 1.00 F-type are potent activators of the h u m a n fat cell adenylate cyclase [9]. In terms of the negative feed-back concept the physiological meaning of these findings a p p e a r e d to be difficult to assess.…”
Section: Lipolysismentioning
confidence: 99%
See 1 more Smart Citation